Systemic stimulation of TLR2 impairs neonatal mouse brain development. - Xiaonan Du; Bobbi Fleiss; Hongfu Li; Barbara D'angelo; Yanyan Sun; Changlian Zhu; Henrik Hagberg; Ofer Levy; Carina Mallard; Xiaoyang Wang (PLoS ONE)
Background Inflammation is associated with perinatal brain injury but the underlying mechanisms are not completely characterized. Stimulation of Toll-like receptors (TLRs) through specific agonists induces inflammatory responses that trigger both innate and adaptive immune responses. The impact of engagement of TLR2 signaling pathways on the neonatal brain is still unclear. The aim of this study was to investigate the potential effect of a TLR2 agonist on neonatal brain development. Methodology/principal findings Mice were injected intraperitoneally (i.p.) once a day from postnatal day (PND) 3 to PND11 with endotoxin-free saline, a TLR2 agonist Pam(3)CSK(4) (5 mg/kg) or Lipopolysaccharide (LPS, 0.3 mg/kg). Pups were sacrificed at PND12 or PND53 and brain, spleen and liver were collected and weighed. Brain sections were stained for brain injury markers. Long-term effects on memory function were assessed using the Trace Fear Conditioning test at PND50. After 9 days of Pam(3)CSK(4) administration, we found a decreased volume of cerebral gray matter, white matter in the forebrain and cerebellar molecular layer that was accompanied by an increase in spleen and liver weight at PND12. Such effects were not observed in Pam3CSK4-treated TLR 2-deficient mice. Pam3CSK4-treated mice also displayed decreased hippocampus neuronal density, and increased cerebral microglia density, while there was no effect on caspase-3 or general cell proliferation at PND12. Significantly elevated levels of IL-1β, IL-6, KC, and MCP-1 were detected after the first Pam3CSK4 injection in brain homogenates of PND3 mice. Pam(3)CSK(4) administration did not affect long-term memory function nor the volume of gray or white matter. Conclusions/significance Repeated systemic exposure to the TLR2 agonist Pam(3)CSK(4) can have a short-term negative impact on the neonatal mouse brain.